2015
DOI: 10.1071/rdv27n1ab198
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to: 198 AGE EFFECT ON RELATIVE GENE EXPRESSION OF BOVINE SPERMATOGONIA

Abstract: Spermatogonial stem cells (SSCs) have important applications in treatments for infertility and animal transgenesis. However, the isolation of bovine SSCs is less efficient than for other species and it is lower for adult bulls. The goal of this study was to verify whether the relative gene expression of spermatogonia is affected by age after the laminin differential plating. Ten grams of parenchyma of testicles from pre-pubertal animals (5 months of age, n = 5) and bulls (3–4 years of age, n = 5) were minced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Spermatogonial stem cells (SSCs) have important applications in treatments for infertility and production of animal transgenesis (Giassetti et al 2015). Studies have shown that the establishment of multipotent male germline stem cell (mGSC) lines derived from neonate and adult testes has been achieved (Mardanpour et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatogonial stem cells (SSCs) have important applications in treatments for infertility and production of animal transgenesis (Giassetti et al 2015). Studies have shown that the establishment of multipotent male germline stem cell (mGSC) lines derived from neonate and adult testes has been achieved (Mardanpour et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The gene targeting based on GSC is a promising technique for the production of transgenic offspring, acting as a valuable tool in bovine research. However, the isolation of bovine's SSCs is less efficient than that of other species (Giassetti et al 2015). In this study, we isolated and established pluripotent mGSCs lines from Chinese Qinchuan bovine testes with the usage of serum-and feeder-free medium, their multipotency and differentiation potential in vitro were also tested.…”
Section: Introductionmentioning
confidence: 99%